2019
DOI: 10.1080/0309877x.2019.1673326
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness among international students in the UK

Abstract: This small scale mixed methods study aims to explore loneliness in an international student population in a single university. Further, to explore the relationship of loneliness in an international student to international student support service use. Design:A convergent parallel mixed method design. An online Jong Gierveld loneliness scale with some additional demographics provided the quantitative data on loneliness in international student population.The qualitative semi-structured interviews explored what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Doing so, they are increasingly focusing upon the social norms and ideals that people use to weigh up their relationships and encounters. These norms include judgements about how many friends is enough, how often friends should see each other, what friends should talk about and what we should do together (Wawera & McCamley, 2020 , p. 1263). These standards vary from place to place, over time and through the life cycle (Alberti, 2019 ).…”
Section: Loneliness and Its Geographiesmentioning
confidence: 99%
“…Doing so, they are increasingly focusing upon the social norms and ideals that people use to weigh up their relationships and encounters. These norms include judgements about how many friends is enough, how often friends should see each other, what friends should talk about and what we should do together (Wawera & McCamley, 2020 , p. 1263). These standards vary from place to place, over time and through the life cycle (Alberti, 2019 ).…”
Section: Loneliness and Its Geographiesmentioning
confidence: 99%
“…International students need to adapt to new social norms to interact effectively with people in the host country and develop new social connections within the new culture they encounter to rebuild identities and create new social networks (Lin & Kingminghae, 2014;Suprapto et al, 2019). For these students, their life in a new country is generally stressful, and they usually experience some degree of loneliness (Tsai et al, 2017;Wawera & McCamley, 2020), which refers to negative feelings of social isolation when people perceive deficiencies in the quantity and quality of their social interactions (Jiang et al, 2018). Because high levels of loneliness correlate strongly with high levels of anxiety and depression and low levels of university satisfaction in international students (Imai, 2017;Misirlis et al, 2020), addressing loneliness is important to improve their mental health and well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies conducted in Western countries, such as the United Kingdom and the United States, have investigated challenges encountered by international students and observed that loneliness is a common experience in this population, which, in turn, decreases their well-being (Girmay & Singh, 2019;Sawir et al, 2008;Wawera & McCamley, 2020). To increase well-being in international students, leisure that is accessible to them (Zhang et al, 2022) is suggested to facilitate their social support (Lee et al, 2018), which correlates negatively with loneliness (Lin & Kingminghae, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another state, which causes loneliness is living away from closer relations and loved ones. a study revealed that students from all over the world living in academic hostels of America have a feeling of being lonely (Wawera & McCamley, 2019). Loneliness is defined as "A complex set of feelings that occurs when intimate and social needs are not adequately met" (Cacioppo et al, 2006(Cacioppo et al, , p.1055).…”
Section: Lonelinessmentioning
confidence: 99%